Gendered preferences: How women's inclusion in society shapes negotiation occurrence in intrastate conflicts. (May 2021) - Nagel, Robert Ulrich
To what extent do gender relations in society influence the likelihood of negotiations during intrastate disputes? A substantial body of literature recognizes gendered inequalities as integral to understanding conflict, yet they have received little attention in systematic studies of conflict management. I argue that patriarchal gender relations that reflect a preference for masculinity over femininity influence states' propensity to negotiate with rebels. I draw on the concept of practices to explain how gender relations shape government preferences for negotiations. Specifically, I contend that practices of excluding women from fully participating in public life institutionalize violence as the preferred way of managing conflict. The implication is that countries with more patriarchal gender relations are less likely to engage in negotiations during intrastate conflicts. I test this argument on all civil conflict dyads between 1975 and 2014. The analyses show that countries that marginalize women's participation in public life are significantly less likely to engage in negotiations. The results provide strong support for my theoretical argument and offer systematic evidence in support of core claims of the feminist peace theory.